Effects of Oil Price Shocks on German Business Cycles - Torsten Schmidt; Tobias Zimmermann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
In this paper we analyse to what extent movements in oil prices can help to explain business cycle fluctuations in Germany.We proceed in several steps:As a starting point we use a standard real business cycle model for the German economy and introduce energy as an additional factor in the production function. As in Kim/Loungani (1992) our finding is that oil price shocks increase the volatility of output but only to a limited extent.We therefore continue by using a real business cycle model for a small open economy and again include energy use in the production function (de Miguel et al. 2003).But compared to our previous model we could only find an additional increase in volatility of output under certain conditions. Subsequently,we use these models to analyse whether the impact of oil price movements has changed over time by splitting our data set into two subsamples: the first from 1970 to 1986 and the second from 1987 to 2002.The main results suggest that the reduced importance of energy for industrial production substantially decreases the vulnerability of the German economy with regard to oil price shocks.
Keywords: E32; 330; Oil prices; business cycle; small open economy